Fic : why fanfiction is taking over the world - Jamison, Anne Elizabeth, 1969- (Dallas, Texas : Smart Pop, an imprint of BenBella Books, Inc., 2013)
Explores the history and culture of fanwriting and how it has transformed popular culture as well as reading, writing, and authorship, and includes discussions from both professional and fan writers.
Writing from sources. The Sherlock Holmes material: a study in fanfic -- A selective history of media fandom. Science fiction, Star Trek, and the birth of media fandom ; Interlude: growing up fic ; The X-Files, Buffy, and the rise of the Internet Fic Fandoms ; Megafandoms: Harry Potter and Twilight -- Fic and publishing -- Fanwriting today -- Fanfiction and writers who don't write fanfiction.
Includes bibliographical references (pages 398-408) and index.
Keywords: Fan fiction -- History and criticism; Literature and the Internet